2022
DOI: 10.3390/ijerph19074051
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Tobacco Smoking in Vehicles, Indoor, and Outdoor Settings in Germany: Prevalence and Associated Factors

Abstract: Little is known on whether secondhand smoke (SHS) exposure in vehicles, indoor, and outdoor settings is similarly patterned in terms of different socio-epidemiological indicators in Germany. This study aims to estimate the current national-level prevalence and associated socio-epidemiological indicators of SHS exposure in vehicles, indoor, and outdoor settings in the German population, using current data from a representative household survey. We used cross-sectional data (N = 3928 respondents aged 14–99 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Moreover, staying in selected public places (eg, bars and restaurants) may be associated with a greater risk of exposure to secondhand smoke 5. Findings from the cross-sectional surveys among adolescents and young adults also showed that a markable proportion of youth may be exposed to secondhand smoke in cars and private vehicles 6 7. Moreover, sociodemographic factors such as educational level, financial situation and individual health literacy levels may influence the risk of exposure to secondhand smoke 3–6…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, staying in selected public places (eg, bars and restaurants) may be associated with a greater risk of exposure to secondhand smoke 5. Findings from the cross-sectional surveys among adolescents and young adults also showed that a markable proportion of youth may be exposed to secondhand smoke in cars and private vehicles 6 7. Moreover, sociodemographic factors such as educational level, financial situation and individual health literacy levels may influence the risk of exposure to secondhand smoke 3–6…”
Section: Introductionmentioning
confidence: 99%